THE PSYCHOSOCIAL AND STRUCTURAL IMPACTS OF NEOCOLONIAL PRACTICES ON CONTEMPORARY EASTERN CONFLICTS IN THE GAZA STRIP AND SUDAN - dos Santos, Aloísio Cássio; Gomes , Nicolle Letícia Osti; da Silva, Ana Beatriz Cardoso; Stefaneli, Giovana Cervantes (Seven Editora, 2024)
The conflicts in the Gaza Strip and Sudan have profound psychosocial and structural impacts on local populations. In Gaza, years of violence, blockades and military operations result in collective trauma, anxiety and social disintegration, especially among children and young people, who grow up in an environment of insecurity and deprivation. In Sudan, conflicts, such as those in Darfur and South Sudan, have roots in ethnic, political, and economic divisions, aggravated by neocolonial practices, which lead to forced displacement, hunger, destruction of infrastructure, and marginalization, perpetuating cycles of poverty and violence. In both regions, structural violence and neocolonialism hinder human development and stability. The analysis of the documentary Gaza (2019) reveals the psychological and social impacts of war, highlighting the resilience and survival strategies of the inhabitants, while the book I am Malala (2013) offers reflections on resistance against oppression, the right to education, and empowerment in conflict contexts. These elements show how neocolonial practices perpetuate inequalities, collective traumas, and sociopolitical instability. The analysis uses both quantitative and qualitative approaches to understand the complexity of the data, showing that conflicts not only disrupt societies but also demonstrate human resilience and the need for global action to promote peace and justice. Thus, the narrative exposes the importance of addressing the roots of inequalities to mitigate the impacts of these conflicts. DOI:https://doi.org/10.56238/sevened2024.037-058